PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK BERBASIS PREDICT-OBSERVE-EXPLAIN MATERI KALOR UNTUK MENINGKATKAN KETERAMPILAN PROSES SAINS - Purnama, Angga Eka; Sujana, Atep; Julia, Julia (Jurnal Pena Ilmiah, 2019)
Students Worksheets (LKPD) are one of the important teaching materials used to make learning more meaningful and develop science process skills (KPS) of students to investigate the environment. During this time educators only use LKPD without analyting it first, so the LKPD is less demanding for students to investigate problems. The purpose of this research is to develop LKPD based on Predict-Observe-Explain (POE) to improve the KPS. The method used in this research is Research and Development (RD). The main instruments are POE based LKPD, validation sheet and poll. LKPD is tested to the students of the class V in four different elementary schools located in the district Sumedang Selatan, Sumedang, West Java. From the research data showed that the KPS of learners increased (95%) after acquired LKPD as needed, LKPD validation result (95%) "excellentâ€ of students as well (88.3 in terms of material 83.5 design) "is very valid" from judgment. The KPS have not been reached primarily on indicators of interpretation and filing questions.